2022
DOI: 10.3390/plants11192628
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory Amplifies Adverse Effects of Drought on Seedling Recruitment in a Keystone Species of Western North American Rangelands

Abstract: Biotic interactions can affect a plant’s ability to withstand drought. Such an effect may impact the restoration of the imperiled western North American sagebrush steppe, where seedlings are exposed to summer drought. This study investigated the impact of herbivory on seedlings’ drought tolerance for a keystone species in this steppe, the shrub Artemisia tridentata. Herbivory effects were investigated in two field experiments where seedlings were without tree protectors or within plastic or metal-mesh tree pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
0
2
0
2
Order By: Relevance
“…Se ha señalado que la interacción entre la sequía y la defoliación por herbivoría puede resultar en la mortalidad de las plantas (Anderegg et al 2015). Algunos estudios han demostrado que la sinergia entre estos factores afectan directamente la tasa de crecimiento relativa de pastos en China (Zhao et al 2008) y arbustos en norte América (Geisler et al 2022). En este trabajo se reporta que plántulas de G. ulmifolia y P. dulce la combinación de los factores estresantes magnificaron el impacto negativo del estresor (disponibilidad de agua) y la perturbación (defoliación) sobre la tasa de crecimiento relativo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se ha señalado que la interacción entre la sequía y la defoliación por herbivoría puede resultar en la mortalidad de las plantas (Anderegg et al 2015). Algunos estudios han demostrado que la sinergia entre estos factores afectan directamente la tasa de crecimiento relativa de pastos en China (Zhao et al 2008) y arbustos en norte América (Geisler et al 2022). En este trabajo se reporta que plántulas de G. ulmifolia y P. dulce la combinación de los factores estresantes magnificaron el impacto negativo del estresor (disponibilidad de agua) y la perturbación (defoliación) sobre la tasa de crecimiento relativo.…”
Section: Discussionunclassified
“…Teóricamente, el impacto de la interacción entre estresores en el funcionamiento de las plantas puede ser aditiva (el efecto de los estresores se suma), antagonista (el impacto es menor a la suma de los efectos), y de sinergia (el impacto combinado de los factores se magnifica más allá de la suma de los impactos individuales) (Bansal et al 2013). Se considera que las interacciones de sinergia son las principales responsables de la pérdida acelerada de la biodiversidad y del funcionamiento de los ecosistemas (Darling et al 2010), y aunque al parecer son menos comunes, en comparación con las interacciones antagonistas y aditivas (Darling & Côté 2008, Tekin et al 2020, existe evidencia, que la interacción entre sequía y herbivoría magnifican el impacto negativo en la respuesta de las plantas (Zhao et al 2008, Geisler et al 2022, incluso con efectos letales (Anderegg et al 2015). Y aunque pocos estudios lo han documentado (Anderegg et al 2015), el efecto de la interacción entre factores estresantes se puede cuantificar al comparar el valor del efecto observado con el efecto aditivo esperado y el intervalo de confianza de la interacción entre los factores (Darling & Côté 2008, Darling et al 2010, Bansal et al 2013.…”
unclassified
“…Also, in this experiment, each seedling was within a metal-mesh protector. In a previous study [ 88 ], we observed that these protectors minimized herbivory and increased survival compared to Vexar protectors typically used in many outplantings. High survival rates could also reflect biotic characteristics of the site.…”
Section: Discussionmentioning
confidence: 99%
“…All seedlings were watered immediately after outplanting through a PVC tube inserted vertically to about 20 cm from the soil surface. Each seedling was enclosed within a metal tree protector (6 mm mesh and close at the top) [ 88 ]. The watering was repeated two weeks later; after that, plants only received natural precipitation.…”
Section: Methodsmentioning
confidence: 99%